A JAK-STAT pathway target gene encoding a single WAP domain (SWD)-containing protein from Litopenaeus vannamei. Issue 89 (June 2019) - Yang, Linwei; Luo, Mengting; He, Jianhui; Zuo, Hongliang; Weng, Shaoping; He, Jianguo; Xu, Xiaopeng
Abstract: In shrimp, the JAK-STAT pathway is essentially implicated in both antiviral and antibacterial responses. However, few regulatory target genes of the JAK-STAT pathway in shrimp have been reported so far. In this study, a novel single WAP domain-containing peptide (LvSWD4) was identified from Pacific white shrimp Litopenaeus vannamei. The promoter of LvSWD4 was predicted to harbor multiple STAT-binding DNA motifs. Over-expression of the JAK-STAT pathway components STAT, JAK and Domeless in vitro significantly enhanced the transcriptional activity of the LvSWD4 promoter, and in vivo silencing of STAT and the the JAK-STAT pathway upstream regulator IRF down-regulated the expression of LvSWD4, suggesting that LvSWD4 could be a target gene of the JAK-STAT pathway. The expression of LvSWD4 was significantly increased after infection with Gram-negative and positive bacteria, fungi and virus, and silencing of LvSWD4 increased the susceptibility of shrimp to V. parahaemolyticus and WSSV infections. In vitro experiments also demonstrated that the recombinant LvSWD4 protein had significant inhibitory activities against Gram negative bacteria V. parahaemolyticus and E. coli and Gram positive bacteria S. aureus and B. subtilis. Furthermore, silencing of LvSWD4 in vivo significantly affected expression of various immune functional genes and attenuated the phagocytic activity of hemocytes. These suggested that as a target gene of STAT, LvSWD4 was essentially implicated in shrimp immunity, which could constitute part of the mechanism underlying the immune function of the shrimp JAK-STAT pathway. Highlights: Identification of a novel SWD gene (LvSWD4) from Litopenaeus vannamei. Expression of LvSWD4 is regulated by the JAK-STAT pathway. Recombinant LvSWD4 protein has antibacterial activity. LvSWD4 is involved in antibacterial and antiviral responses and immune regulation.